PENERAPAN MODEL PEMBELAJARAN KOOPERATIF DENGAN LKPD WORD SQUARE UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF IPA SISWA KELAS VII SMP NEGERI 2 PERANAP PADA MATERI TATA SURYA - Riga, Riga; Azhar, Azhar; Zuhdi, Zuhdi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This study was aim to determine the differences in students' cognitive science learning outcomes by applying cooperative learning models with LKPD word square with conventional learning. This research conducted at SMP Negeri 2 Peranap on Mei 2018. Two groups of samples were choose from homogeneous classes. Quasi experiments with posttest only non-equivalent control group design used in this study. The data obatained from cognitive learning result test which consisted of 15 items multiple choice. Descriptive and inferential analysis used for data analysis. Based on descriptive analysis, the average of skor in experimental class was 80,36 and 71,4 for control class, this indicated student’s learning result in experimental class was higher than control class. Based on inferential analysis through independent sample t test sig value. (2-tailed) = 0.300 < 0.05. This mean was a significant differences. Thus it concluded that the use of cooperative learning model with LKPD word square can enhance student’s learning outcomes in VII class SMP Negeri 2 Peranap of solar system material.Keywords: Cognitive Learning Outcomes, Cooperative Learning Model, LKPD Word Square, Solar System